Association of Dietary Phytosterols Intake and Survival of Esophageal Squamous Cell Carcinoma: A Prospective Cohort Study. (26th November 2022) - Wang, Shuyi; Zhao, Wenjing; Li, Jun; Hu, Peng; Zhao, Yue; Tse, Lap-Ah; Lu, Jiahai; Ren, Zefang; Xing, Xiangbing; Liu, Xudong
Abstract: Background: The association of dietary phytosterols intake with survival of esophageal squamous cell carcinoma (ESCC) remains unclear. This study was to examine the effect of dietary phytosterols intake on ESCC survival in a Chinese rural population. Methods: A total of 942 incident ESCC patients diagnosed between 2011 and 2013 in Yanting area were followed up until March 1 st, 2020. Dietary intake five years before ESCC diagnosis was collected using a food frequency questionnaire. The outcome of interest was all-cause mortality. Cox proportional hazards regression model was used to estimate hazard ratio (HR) and 95% confidence intervals (CI). Results: When comparing the highest with lowest intake quartiles, intake of five specific and total phytosterols was not significantly associated with risk of death after adjustment for covariates, the adjusted HR (95% CI) for β-sitosterol, campesterol, stigmasterol, β-sitostanol, campestanol and total phytosterols was 0.90 (95% CI: 0.70-1.16), 0.92 (95% CI: 0.71-1.19), 0.86 (95% CI: 0.66-1.12), 0.93 (95% CI: 0.73-1.20), 0.94 (95% CI: 0.72-1.21), 0.89 (95% CI: 0.69-1.15), respectively. Conclusion: This study does not find any association between pre-diagnostic phytosterols intake and risk of all-cause mortality among ESCC patients. Further research is required to determine the effect of post-diagnostic phytosterols intake on ESCC survival.